Predictors of Acquired Perforating Dermatosis in Uremic Patients on Hemodialysis: A Case-Control Study. (11th December 2012) - Weng, Cheng-Hao; Hu, Ching-Chih; Ueng, Shir-Hwa; Yu, Chun-Chen; Hui, Chung-Yee; Lin, Ja-Liang; Yang, Chih-Wei; Hung, Cheng-Chieh; Hsu, Ching-Wei; Yen, Tzung-Hai
Abstract : Objectives . The purpose of this study was to identify the predictors of acquired perforating dermatosis (APD) in patients on maintenance hemodialysis (HD). Methods . A case-control study was performed at our outpatient HD center between January 1, 2000 and March 31, 2011. Patients on HD with APD were matched (1 : 2) for gender and age with controls on HD. Conditional logistic regression was used to identify factors associated with APD. Results . A total of 19 patients with APD and 38 age and gender matched patients were enrolled in the study. Univariate logistic regression showed that APD was significantly associated with diabetes mellitus (DM), reduced levels of intact parathyroid hormone (iPTH) and albumin (Alb), reduced dialysis adequacy (K t / V ) and urea reduction rate (URR), and elevated levels of high-sensitivity C-reactive protein (hsCRP). Multivariate logistic regression identified reduced iPTH (hazard ratio (HR): 0.983; P = 0.026 ) and Alb (HR: 0.099; P = 0.047 ) and elevated hsCRP (HR: 1.210, P = 0.024 ) as risk factors for APD. Conclusions . iPTH, hsCRP, and Alb are predictors for APD in HD patients.